Study of Atmospheric Pollutants Concentration Correlation with Meteorological Quantities in Bandar Abbas - Marziyeh Sisipoor; Mehdi Rahnama; Saviz Sehat Kashani; Noshin Khodam; faezeh noori; Sajad Qahramani (Nīvār)
Air pollution and its pollutants affect human health and the environment. Knowing the factors contributing to air pollution is crucial in mitigating its impacts on industrial cities. Therefore, evaluating atmospheric pollutants concentration correlation with meteorological quantities in Bandar Abbas is considered as the main purpose of this study special economic zone. During a statistical period of one year, data from the Bandar Abbas synoptic weather station was utilized, which included measurements of wind, temperature, pressure, relative humidity, horizontal visibility, and concentration of atmospheric pollutants from the station located in the Bandar Abbas. Behavioral studies were conducted to investigate the correlation between pollutants and meteorological quantities seasonally, monthly, and daily. Also, by calculating the air quality index, the daily status of the air quality and pollutant index was determined. In general, the results of this study showed that the main reason of urban pollution in Bandar Abbas city was the abundance of two particulate pollutants, PM10 and PM2.5, and these conditions are also dependent on the weather systems and climatic conditions of the region. The daily average correlation analysis of PM10 pollutant showed that on a daily scale, this pollutant had a significant and positive relationship with wind speed and a significant and inverse relationship with relative humidity and horizontal visibility. PM2.5 pollutant showed an inverse and significant relationship with temperature and horizontal visibility